Influences of the coconut water and sucrose on the embryogenic callus induction and the clonal embryo formation of Phalaenopsis amabilis (L.) Blume - Nhut, Duong Tan; Tram, Hong Ngoc; Huy, Nguyen Phuc; Khiem, Dinh Van (Academia Journal of Biology, 2012)
Phalaenopsis amabilis (L.) Blume (Orchidaceae) is one of many commercial valuable orchids as cut flowers and potted plants throughout the world. Considerable difficulties have been encountered in the clonal propagation of this orchid due to the characteristics ununiform and the limited plantlets number. In this paper, an established method of the Phalaenopsis amabilis propagation through embryogenesis callus was described. The in vitro leaves emerging from the flower stalk nodes were used for protocorm-like bodies (PLBs) induction. These PLBs were used for the embryogenesis callus (callus) induction. About 1455 mg calli without any morphological change were harvested from 70 mg calli on 30 ml MS medium supplemented with 2 mg/l BA, 0.5 mg/l NAA, 20% (v/v) CW, 1 g/l activated charcoal (AC), 30 g/l sucrose and 9 g/l agar after 5 culture weeks of. On the same medium without sucrose, 70 mg calli produced 1841 mg PLB (approximately 200 PLBs) after 5 weeks of culture; data also showed that PLB fresh weight and quantity in the nylon film culture system (NF) were almost equal to that in conventional system (C). The hyponex medium supplemented with 0.5 mg/l NAA, 2 mg/l BA, 30 g/l sucrose, 1 g/l AC and 15% (v/v) CW was used for the plantlet regeneration from PLB. The results showed that plantlet quantity obtained in NF system (185 plantlets) was higher than that in C system (109 plantlets) after 2 culture months. Phalaenopsis amabilis plantlets in NF system had much high survival rate (95%) than that in C system (70%) after 4 weeks transferred in the greenhouse.